2019
DOI: 10.1200/jco.2019.37.4_suppl.531
|View full text |Cite
|
Sign up to set email alerts
|

The role of Parvimonas micra in intestinal tumorigenesis in germ-free and conventional APCmin/+ mice.

Abstract: 531 Background: Our in-house meta-analysis of fecal shotgun metagenomic sequences from colorectal cancer (CRC) and control subjects from four cohorts of various ethnicities identified a higher abundance of Parvimonas micra in CRC. We aimed to investigate the effect of P. micra in colon tumor formation and development. Methods: We collected 309 fecal samples and 259 colon biopsies from patients with CRC, advanced adenoma and healthy subjects. P. micra strain was isolated from the feces of a CRC patient. APC mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…It has also been reported that P. micra may be involved in gut bacterial translocation and the upregulation of interleukins in the tumor microenvironment (55). A previous study demonstrated that APC Min/+ mice gavaged with P. micra exhibited a significantly higher tumor burden and tumor load, and cell proliferation was significantly higher in the colon tissues of P. micra gavaged germ-free mice compared with control mice (56). Furthermore, the tumor promoting effect of P. micra has been reported to be associated with altered immune responses and increased inflammation in the gut (50,56).…”
Section: Discussionmentioning
confidence: 93%
“…It has also been reported that P. micra may be involved in gut bacterial translocation and the upregulation of interleukins in the tumor microenvironment (55). A previous study demonstrated that APC Min/+ mice gavaged with P. micra exhibited a significantly higher tumor burden and tumor load, and cell proliferation was significantly higher in the colon tissues of P. micra gavaged germ-free mice compared with control mice (56). Furthermore, the tumor promoting effect of P. micra has been reported to be associated with altered immune responses and increased inflammation in the gut (50,56).…”
Section: Discussionmentioning
confidence: 93%
“…Mice treated with azoxymethane had a higher incidence of intestinal dysplasia following exposure to P. anaerobius . APC Min/+ mice gavaged with P. micra exhibited higher tumor burden and tumor load . However, their carcinogenic mechanisms have not been fully elucidated.…”
Section: Identification Of Colorectal Cancer‐associated Microbiota Bamentioning
confidence: 99%
“…25 APC Min/+ mice gavaged with P. micra exhibited higher tumor burden and tumor load. 26 However, their carcinogenic mechanisms have not been fully elucidated. In contrast to gastric cancer, which is caused mostly by a single species, Helicobacter pylori, CRC can be affected by various gut bacteria and their coexistence networks.…”
Section: Identific Ation Of Colorec Tal C An Cer-a Sso Ciated Mi Crmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a producer of collagenase and of limited elastolytic and hemolytic activity [Ota-Tsuzuki and Alves Mayer 2010]. In a mouse CRC model, P. micra elicited increased Th2 and Th17 cells, decreased Th1 cells and increased inflammation [Yu et al 2019].…”
Section: Cohort Specific Speciesmentioning
confidence: 99%